2016
DOI: 10.1139/cjss-2015-0081
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentration in soil in the tailing dam vicinity of an old gold mine in Johannesburg, South Africa

Abstract: Soil contamination with heavy metals is a serious concern to food production and human health. The present study was conducted to evaluate the impact of tailings from an old mining site on heavy metal contamination of soil. Using a GPS to map out different sites around the tailing dam, soil samples were taken from under grassland at the different sites, at depths of 15 cm and 1 m, using a shovel and handheld auger. The samples were prepared, acid digested, and analyzed for a multi-element suite by inductively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The average As levels (16 mg/kg) reported in this study are in the range reported in residential soil studies conducted in other parts of South Africa, such as Limpopo Province (0.2–25 mg/kg) [ 6 ] and the city of Johannesburg (0.1–65) [ 7 ]. On the other hand, the average Mn (137 mg/kg), Pb (30 mg/kg), Sr (176 mg/kg) and Zn (232 mg/kg) levels were much higher than the levels reported in mine tailings of Johannesburg; Mn (43 mg/kg), Pb (17 mg/kg), Sr (2 mg/kg) and Zn (49 mg/kg) [ 50 ]. Levels of Zn were also much higher in Kuils River than those observed in a Ugandan study, in which Namuhani et al [ 1 ] reported a mean concentration of 28 mg/kg around a steel mill in that country.…”
Section: Discussionmentioning
confidence: 99%
“…The average As levels (16 mg/kg) reported in this study are in the range reported in residential soil studies conducted in other parts of South Africa, such as Limpopo Province (0.2–25 mg/kg) [ 6 ] and the city of Johannesburg (0.1–65) [ 7 ]. On the other hand, the average Mn (137 mg/kg), Pb (30 mg/kg), Sr (176 mg/kg) and Zn (232 mg/kg) levels were much higher than the levels reported in mine tailings of Johannesburg; Mn (43 mg/kg), Pb (17 mg/kg), Sr (2 mg/kg) and Zn (49 mg/kg) [ 50 ]. Levels of Zn were also much higher in Kuils River than those observed in a Ugandan study, in which Namuhani et al [ 1 ] reported a mean concentration of 28 mg/kg around a steel mill in that country.…”
Section: Discussionmentioning
confidence: 99%
“…The Gauteng province of South Africa is characterized by numerous mine tailing dumps which are a result of previously active mining activities. Several decades of mining activities in the Gauteng Province of South Africa has had and continues to have a negative impact on ecosystems through the pollution of soils and water with high levels of potentially toxic metals such as As, Pb, and Al, as is the case with the old gold mine tailings in Blesbokspruit, Ekurhuleni South Africa [6][7][8][9]. Previous studies have reported cases of health-related complications among dwellers who reside nearer to these mine tailing sites as a result of the contamination of agricultural soils, water sources, and atmospheric air by these mine tailings and effluents [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the Copperbelt Province of Zambia, decommissioned mine tailings have resulted in extensive mine waste dumpsites that are contaminating water and soils, especially in Kitwe and Mufulira districts. Therefore, there is serious concern over the adverse effect of mine waste on the ecosystem, biodiversity, and health of people residing in the vicinity of these mine waste dumpsites 1 , 16 – 18 . Previous studies investigated the level of heavy metal pollution in soil, plants, and water and their probable impact on the environment in the Copperbelt Province 17 , 19 – 22 .…”
Section: Introductionmentioning
confidence: 99%